A positive electrode material and preparation method thereof, and sodium ion battery
By coating the surface of the sodium ferric sulfate material with sodium ferric sulfate fluorophosphate and a carbon layer to form a double-layer coated composite positive electrode material, the problems of the sodium ferric sulfate material being sensitive to moisture and having an excessively high platform voltage are solved, thus achieving a positive electrode material with low cost, high capacity and excellent cycle performance.
Patent Information
- Application Number
- CN202411132322.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2044-08-19
AI Technical Summary
Sodium iron sulfate positive electrode material is sensitive to moisture, its structure is easily destroyed, its platform voltage is too high, and it is difficult to adapt to low-cost electrolytes, which limits its practical application.
Sodium ferric sulfate fluorophosphate nanomaterials and a carbon layer are coated on the surface of the sodium ferric sulfate material to form a double-layer coated composite positive electrode material, which improves air stability and ion conductivity and constructs an excellent ion/electron transfer channel.
The air stability and cycle performance of sodium ferric sulfate are improved, the structural stability and ionic conductivity of the material are improved, the cost is reduced, and the capacity of the material under high voltage is enhanced.
Smart Images

Figure CN119029171B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the vigorous development of the global new energy industry, a green, low-carbon, circular economic system is gradually taking shape. Sodium-ion batteries, a promising technology for electric vehicles and stationary energy storage, offer advantages over lithium-ion batteries, such as excellent low-temperature performance, low cost, and abundant materials.
[0003] Currently, sodium-ion cathode materials include layered oxides, polyanions, and Prussian blue-based cathode materials. The structural phase transitions of layered oxides introduce numerous instabilities during sodium ion intercalation and deintercalation, and the high cost of introducing expensive Ni and Cu elements to improve performance hinders large-scale future market adoption. Prussian blue-based materials contain numerous Fe(CN)6 defects and crystalline water in their structures, leading to structural failure and gas production during sodium ion intercalation and deintercalation, making commercial application difficult. Polyanionic compounds, on the other hand, possess a rigid, open framework capable of stably storing sodium ions. In terms of resource cost, the abundance of Fe in the Earth's crust is 5.00%, far exceeding that of elements like Mn, V, and Co. Iron-based polyanionic compounds offer cost-effectiveness and environmental friendliness.
[0004] Among various iron-based polyanionic compounds, sodium ferric sulfate has the highest redox potential, approximately 3.8V, much higher than sodium ferric pyrophosphate (3.10V) and sodium ferric phosphate (2.90V). Due to its similar reversible capacity, wide raw material sources, and simple preparation process, the energy density, raw material cost, and production cost of sodium ferric sulfate are far superior to other polyanionic compounds. However, sodium ferric sulfate is sensitive to moisture; even a trace amount of water can destroy its structure and form a hydrated phase. In addition, the platform voltage of sodium ferric sulfate is too high, making it difficult to adapt to low-cost electrolytes, which greatly limits its practical application.
[0005] Therefore, there is an urgent need to develop a sodium iron sulfate positive electrode material with stable performance. Summary of the Invention
[0006] The present invention is based on the inventor's discovery and understanding of the following facts and problems: sodium ferric sulfate material is sensitive to moisture, and even a trace amount of water will destroy its structure and form a hydrated phase. In addition, the platform voltage of sodium ferric sulfate is too high, making it difficult to adapt to low-cost electrolytes.
[0007] The present invention aims to address, at least to some extent, one of the technical problems in the related art. To this end, embodiments of the present invention provide a cathode material, a preparation method thereof, and a sodium-ion battery. These materials not only improve the air stability of sodium ferric sulfate but also enhance the material's ionic conductivity, create a more optimal ion / electron transfer pathway, more easily and stably utilize the cathode material's capacity, enhance the material's structural stability at high voltages, and significantly improve the material's cycling performance.
[0008] An embodiment of the present invention provides a positive electrode material, which includes a sodium ferric sulfate material, a sodium ferric sulfate fluorophosphate layer coated on the outside of the sodium ferric sulfate material, and a carbon layer coated on the outside of the sodium ferric sulfate fluorophosphate layer.
[0009] The advantages and technical effects brought by the positive electrode material of the embodiment of the present invention are as follows: by coating a layer of sodium ferric sulfate fluorophosphate nanomaterial on the surface of the sodium ferric sulfate material, and then coating it with a carbon material, a double-layer coated composite positive electrode material is formed with sodium ferric sulfate as the core and the sodium ferric sulfate fluorophosphate nanomaterial and carbon material as the shell. The positive electrode material has low cost, high capacity and excellent cycle performance. The positive electrode material can not only improve the air stability of sodium ferric sulfate, but also improve the ionic conductivity of the material, construct a better ion / electron transfer channel, more easily and stably exert the capacity of the positive electrode material, improve the structural stability of the material under high voltage, and significantly improve the cycle performance of the material.
[0010] In the embodiment of the present invention, by introducing PO4 3- , can improve the air stability of sodium iron sulfate, and can also improve the ionic conductivity of the material, build a better ion / electron transfer channel, more easily and stably play the capacity of the material, improve the structural stability of the material under high voltage, and greatly improve the cycle performance of the material. But PO4 3- The introduction of F will cause the working voltage of the sodium ferric sulfate material to drop, making the voltage of the core and shell materials mismatched. - , the negatively charged fluoride ions can partially replace sulfate and phosphate, forming a more stable metal-fluorine bond, making the metal-ligand bond more ionized, thereby increasing the redox potential, ensuring the consistency of the core and shell voltages, and improving the cyclic stability of the material; at the same time, the stable metal-fluorine bond can reduce the volume change of the material during charging and discharging, change the electronic distribution of the material, improve the conductivity of the electrode, and enhance the cyclic stability of the material. Carbon coating can also improve the specific surface area and conductive properties of the material, resulting in a low-cost, high-capacity, and excellent cyclic performance polyanion positive electrode material. However, when the surface of sodium ferric sulfate is only carbon-coated, the air stability of the material cannot be effectively improved, but the conductive network constructed by the carbon layer can improve the rate performance and cyclic performance of the material to a certain extent.
[0011] In some embodiments, the positive electrode material has a median particle size Dv50 of 3 to 8 μm;
[0012] and / or, the thickness of the sodium ferric sulfate fluorophosphate layer is 10 to 100 nm;
[0013] And / or, the carbon layer has a thickness of 1 to 10 nm.
[0014] In some embodiments, the chemical formula of the sodium ferric sulfate fluorophosphate layer is Na 9- 2x Fe 1.5 (SO4) x (PO4) 3-x F 3-x , where x = 2.0 to 2.9.
[0015] An embodiment of the present invention provides a method for preparing a positive electrode material, comprising the following steps:
[0016] (1) mixing a sodium ferric sulfate precursor with a sodium source, an iron source, a phosphorus source, and a fluorine source, and then ball milling to obtain a mixed solution;
[0017] (2) drying the mixed solution to obtain a sodium ferric sulfate composite material coated with sodium ferric sulfate fluorophosphate;
[0018] (3) mixing the composite material in step (2) and the carbon source, dispersing the mixture, filtering, and drying the mixture to obtain a carbon / fluorophosphate-sodium iron sulfate-coated sodium iron sulfate composite material precursor;
[0019] (4) Sintering the composite material precursor in step (3) to obtain a positive electrode material.
[0020] In the embodiments of the present invention, the preparation method is simple, easy to implement, highly safe, and has broad research prospects and application value.
[0021] In some embodiments, in step (1), the mass ratio of the sodium ferric sulfate precursor to the total mass of the sodium source, the iron source, the phosphorus source, and the fluorine source is 90-99:1-10;
[0022] And / or, the molar ratio of the sodium source, iron source, phosphorus source and fluorine source satisfies the chemical formula Na 9-2x Fe 1.5 (SO4) x (PO4) 3-x F 3-x , x=2.0~2.9;
[0023] and / or, the sodium source comprises at least one of sodium sulfate, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate or an organic acid salt of sodium;
[0024] and / or, the iron source comprises at least one of a divalent iron compound;
[0025] And / or, the phosphorus source includes at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium dihydrogen phosphate, sodium hexametaphosphate, and sodium pyrophosphate;
[0026] And / or, the fluorine source includes at least one of sodium fluoride or ammonium fluoride.
[0027] In some embodiments, in step (1), the rotation speed of the ball mill is 200 to 500 r / min;
[0028] And / or, the ball milling time is 2 to 4 hours.
[0029] In some embodiments, in step (2), the drying is performed by spray freeze drying.
[0030] In some embodiments, in step (3), the carbon source includes at least one of acetylene black, biomass-based carbon nanomaterials, glucose, sucrose, caramel, starch, carbon nanotubes, carbon quantum dots, and dextrin;
[0031] and / or, the mass ratio of the composite material to the carbon source is 98-99:0.01-6;
[0032] and / or, the dispersing speed is 500 to 5000 r / min;
[0033] And / or, the dispersion time is 1 to 3 hours.
[0034] In some embodiments, in step (4), the sintering temperature is 300-500°C;
[0035] And / or, the sintering time is 4 to 8 hours.
[0036] An embodiment of the present invention provides a sodium ion battery, which includes the positive electrode material described in the embodiment of the present invention or the positive electrode material prepared by the preparation method described in the embodiment of the present invention.
[0037] In the embodiments of the present invention, the sodium ion battery has all the advantages of the positive electrode material. The positive electrode material can not only improve the air stability of sodium ferric sulfate, but also improve the ionic conductivity of the material, construct a better ion / electron transfer channel, make it easier to stably exert the capacity of the positive electrode material, improve the structural stability of the material under high voltage, and greatly improve the cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the XRD pattern of the positive electrode material in Example 1.
[0039] Figure 21 is a rate performance diagram of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0040] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0041] The present invention provides a positive electrode material, which includes a sodium ferric sulfate material, a sodium ferric sulfate fluorophosphate layer coated on the outside of the sodium ferric sulfate material, and a carbon layer coated on the outside of the sodium ferric sulfate fluorophosphate layer.
[0042] The positive electrode material of the embodiment of the present invention is formed by coating the surface of the sodium ferric sulfate material with a layer of sodium ferric sulfate fluorophosphate nanomaterial, and then coating it with a carbon material, forming a double-layer coated composite positive electrode material with sodium ferric sulfate as the core and the sodium ferric sulfate fluorophosphate nanomaterial and carbon material as the shell. The positive electrode material has low cost, high capacity and excellent cycle performance. The positive electrode material not only improves the air stability of the sodium ferric sulfate, but also improves the material's ionic conductivity, constructs a better ion / electron transfer channel, makes it easier to stably exert the capacity of the positive electrode material, improves the structural stability of the material under high voltage, and significantly improves the material's cycle performance.
[0043] In the embodiment of the present invention, by introducing PO4 3- , can improve the air stability of sodium iron sulfate, and can also improve the ionic conductivity of the material, build a better ion / electron transfer channel, more easily and stably play the capacity of the material, improve the structural stability of the material under high voltage, and greatly improve the cycle performance of the material. But PO4 3- The introduction of F will cause the working voltage of the sodium ferric sulfate material to drop, making the voltage of the core and shell materials mismatched. - , the negatively charged fluoride ions can partially replace sulfate and phosphate, forming a more stable metal-fluorine bond, making the metal-ligand bond more ionized, thereby increasing the redox potential, ensuring the consistency of the core and shell voltages, and improving the cyclic stability of the material; at the same time, the stable metal-fluorine bond can reduce the volume change of the material during charging and discharging, change the electronic distribution of the material, improve the conductivity of the electrode, and enhance the cyclic stability of the material. Carbon coating can also improve the specific surface area and conductive properties of the material, resulting in a low-cost, high-capacity, and excellent cyclic performance polyanion positive electrode material. However, when the surface of sodium ferric sulfate is only carbon-coated, the air stability of the material cannot be effectively improved, but the conductive network constructed by the carbon layer can improve the rate performance and cyclic performance of the material to a certain extent.
[0044] In some embodiments, the positive electrode material has a median particle size Dv50 of 3 to 8 μm, specifically, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or 8 μm. In embodiments of the present invention, a median particle size Dv50 of 3 to 8 μm optimizes the material's performance. When the positive electrode material has a larger median particle size, the material's rate performance is relatively poor; when the positive electrode material has a smaller median particle size, the positive electrode slurry is difficult to process.
[0045] In some embodiments, the median particle size Dv50 of the sodium ferric sulfate material is 3 to 8 μm, specifically, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, and 8 μm.
[0046] In some embodiments, the thickness of the sodium ferric sulfate fluorophosphate layer is 10 to 100 nm, specifically, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, or 100 nm. In embodiments of the present invention, the thickness of the sodium ferric sulfate fluorophosphate layer is 10 to 100 nm, which can improve the air stability of the material and construct an optimal ion / electron transfer channel. A thicker sodium ferric sulfate fluorophosphate layer is not conducive to capacity utilization; a thinner sodium ferric sulfate fluorophosphate layer, relatively speaking, does not effectively improve the air stability of the material.
[0047] In some embodiments, the carbon layer has a thickness of 1 to 10 nm, specifically, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, and 10 nm. In embodiments of the present invention, a carbon layer thickness of 1 to 10 nm can construct an optimal conductive network. A thicker carbon layer is relatively less conducive to capacity utilization, while a thinner carbon layer is less likely to provide a sufficient conductive network.
[0048] In some embodiments, the mass percentage of the carbon layer in the positive electrode material is no higher than 2%, optionally, 1%, 2%.
[0049] In some embodiments, the chemical formula of the sodium ferric sulfate fluorophosphate layer is Na 9- 2x Fe 1.5 (SO4) x (PO4) 3-x F 3-x , wherein x=2.0 to 2.9, specifically, for example, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9. In the embodiment of the present invention, the chemical formula of sodium ferric sulfate fluorophosphate is Na 9-2x Fe 1.5 (SO4) x (PO4) 3- x F3-x , which can improve the stability of the material in the air and make it easier to stably exert the capacity of the composite positive electrode material.
[0050] In some embodiments, the mass percentage of the sodium ferric sulfate material in the positive electrode material is 90%-99%.
[0051] A method for preparing a positive electrode material of the present invention comprises the following steps:
[0052] (1) mixing a sodium ferric sulfate precursor with a sodium source, an iron source, a phosphorus source, and a fluorine source, and then ball milling to obtain a mixed solution;
[0053] (2) drying the mixed solution to obtain a sodium ferric sulfate composite material coated with sodium ferric sulfate fluorophosphate;
[0054] (3) mixing the composite material in step (2) and the carbon source, dispersing the mixture, filtering, and drying the mixture to obtain a carbon / fluorophosphate-sodium iron sulfate-coated sodium iron sulfate composite material precursor;
[0055] (4) Sintering the composite material precursor in step (3) to obtain a positive electrode material.
[0056] In the embodiments of the present invention, the preparation method is simple, easy to implement, highly safe, and has broad research prospects and application value.
[0057] In some embodiments, in step (1), the sodium ferric sulfate precursor is unsintered sodium ferric sulfate. Optionally, the sodium ferric sulfate precursor has a median particle size Dv50 of 3 to 8 μm, specifically, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or 8 μm. In embodiments of the present invention, the sodium ferric sulfate precursor is sintered to remove the hydrated phase to obtain the sodium ferric sulfate material.
[0058] In some embodiments, in step (1), the mass ratio of the sodium ferric sulfate precursor to the total mass of the sodium source, iron source, phosphorus source and fluorine source is 90-99:1-10, specifically, 90-99 (for example, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99):1-10 (1, 2, 3, 4, 5, 6, 7, 8, 9, 10).
[0059] In some embodiments, in step (1), the molar ratio of the sodium source, iron source, phosphorus source, and fluorine source satisfies the chemical formula Na 9-2x Fe 1.5 (SO4) x (PO4) 3-x F 3-x, x = 2.0 to 2.9, specifically, for example, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9. In the embodiment of the present invention, by adjusting the molar ratio of the sodium source, iron source, phosphorus source, and fluorine source, sodium, iron, phosphorus, fluorine, and sulfur can satisfy the chemical formula Na 9-2x Fe 1.5 (SO4) x (PO4) 3-x F 3-x .
[0060] In some embodiments, in step (1), the sodium source includes at least one of sodium sulfate, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate or an organic acid salt of sodium.
[0061] In some embodiments, in step (1), the iron source includes at least one of divalent iron compounds; optionally, the iron source includes at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous phosphate, specifically, for example, ferrous sulfate hydrate.
[0062] In some embodiments, in step (1), the phosphorus source includes at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium dihydrogen phosphate, sodium hexametaphosphate, and sodium pyrophosphate.
[0063] In some embodiments, in step (1), the fluorine source includes at least one of sodium fluoride or ammonium fluoride.
[0064] In some embodiments, in step (1), a sodium ferric sulfate precursor, a sodium source, an iron source, a phosphorus source, a fluorine source, and a solvent are mixed; optionally, the solvent includes water; optionally, the mass ratio of the sodium ferric sulfate precursor to the solvent is 60-80:20-40.
[0065] In some embodiments, in step (1), the ball milling speed is 200 to 500 r / min, optionally, the ball milling speed is the rotation speed of the ball mill, specifically, for example, 200 r / min, 300 r / min, 400 r / min, 500 r / min; the ball milling time is 2 to 4 hours, specifically, for example, 2 hours, 3 hours, 4 hours. In the embodiment of the present invention, ball milling is conducive to the dispersion of the material and can construct a more uniform sodium ferric sulfate fluorophosphate coating layer.
[0066] In some embodiments, in step (1), in order to prevent oxidation of Fe, the ball milling is performed under the protection of an inert gas. Optionally, the inert gas includes nitrogen.
[0067] In some embodiments, in step (2), the drying is performed by spray freeze drying; optionally, the temperature of the spray freeze drying is 60°C to 10°C, specifically, for example, 60°C, 50°C, 40°C, 30°C, 20°C,
[0068] 10°C; the spray freeze drying time is 20 to 60 min, specifically, for example, 20 min, 30 min, 40 min, 50 min, 60 min; optionally, the spray freeze drying is carried out in a spray freeze dryer; the spray freeze drying is carried out under the protection of an inert gas, optionally, the inert gas includes nitrogen.
[0069] In the embodiment of the present invention, spray freeze drying is beneficial to maintaining the uniformity of the coating layer.
[0070] In some embodiments, in step (3), the carbon source comprises at least one of acetylene black, biomass-based carbon nanomaterials, glucose, sucrose, caramel, starch, carbon nanotubes (CNTs), carbon quantum dots, and dextrin. Preferably, the carbon source is low-cost acetylene black. In the embodiments of the present invention, acetylene black, biomass-based carbon nanomaterials, CNTs, and carbon quantum dots are directly coated to form a carbon layer, and glucose, sucrose, caramel, starch, and dextrin are coated by pyrolysis, all of which can improve the electron transport performance of the positive electrode material.
[0071] In some embodiments, in step (3), the mass ratio of the composite material to the carbon source is 98-99:0.01-6, specifically, 98-99 (for example, 98, 98.2, 98.4, 98.5, 98.6, 98.9, 99):0.01-6 (for example, 0.01, 0.1, 1, 1.2, 1.4, 1.5, 1.6, 1.9, 2, 3, 4, 5, 6).
[0072] In some embodiments, in step (3), the composite material, carbon source and solvent in step (2) are mixed; the solvent includes water; optionally, the mass ratio of the composite material to the solvent is 60-80:20-40.
[0073] In some embodiments, in step (3), the dispersion speed is 500 to 5000 r / min, specifically, for example, 500 r / min, 1000 r / min, 2000 r / min, 3000 r / min, 4000 r / min, 5000 r / min; the dispersion time is 1 to 3 hours, specifically, for example, 1 hour, 2 hours, 3 hours. In the embodiments of the present invention, high-speed dispersion can make the carbon distribution uniform, which is conducive to forming a uniform and stable carbon coating layer.
[0074] In some embodiments, in step (3), the dispersing and / or filtering and / or drying is performed under the protection of an inert gas. Optionally, the inert gas includes nitrogen.
[0075] In some embodiments, in step (3), the drying is performed by oven drying; and / or the drying temperature is 150-200°C.
[0076] In some embodiments, in step (4), the sintering is performed under the protection of an inert gas. Optionally, the inert gas includes nitrogen.
[0077] In some embodiments, in step (4), the sintering temperature is 300-500°C, specifically, for example, 300°C, 400°C, 500°C; the sintering time is 4-8h, specifically, for example, 4h, 5h, 6h, 7h, 8h. In the embodiments of the present invention, sintering can improve the crystallinity and electrochemical properties of the material, and the preferred sintering temperature is 300-500°C. When the sintering temperature is too high, sulfate is easily decomposed and the material fails; when the sintering temperature is too low, the consistency and electrochemical properties of the material are poor relative to the preferred sintering temperature.
[0078] In some embodiments, in step (4), the sintered material is post-processed to obtain a positive electrode material; optionally, the post-processing includes at least one of crushing, grinding, pulverizing, screening, and demagnetization; crushing, grinding, and pulverizing can successively reduce the particle size of the material; optionally, the sintered material is successively crushed, ground, and pulverized.
[0079] A sodium ion battery according to an embodiment of the present invention comprises a positive electrode material according to an embodiment of the present invention or a positive electrode material prepared by a preparation method according to an embodiment of the present invention.
[0080] In the embodiments of the present invention, the sodium ion battery has all the advantages of the positive electrode material. The positive electrode material can not only improve the air stability of sodium ferric sulfate, but also improve the ionic conductivity of the material, construct a better ion / electron transfer channel, make it easier to stably exert the capacity of the positive electrode material, improve the structural stability of the material under high voltage, and greatly improve the cycle performance of the material.
[0081] In some embodiments, the sodium ion battery further comprises a negative electrode material, a separator and an electrolyte containing sodium ions; optionally, the negative electrode material comprises at least one of graphene, graphene oxide, soft carbon, hard carbon, expanded graphite, silicon, and mesophase carbon microbeads, preferably hard carbon.
[0082] The present invention is described below with reference to specific examples. It should be noted that these examples are merely illustrative and do not limit the present invention in any way.
[0083] Example 1
[0084] A method for preparing a positive electrode material comprises the following steps:
[0085] (1) 97 parts of sodium ferric sulfate precursor (6 μm) and 3 parts of sodium source, iron source, phosphorus source and fluorine source were mixed and uniformly dispersed in solvent water in a mixing device, and high-speed ball milling was performed at 300 r / min under nitrogen protection for 3 h to obtain a mixed solution, wherein the molar ratio of sodium source, iron source, phosphorus source and fluorine source met Na 3.6 Fe 1.5 (SO4) 2.7 (PO4) 0.3 F 0.3 , x=2.7; wherein the sodium source is sodium sulfate, the iron source is ferrous sulfate heptahydrate, the phosphorus source is sodium dihydrogen phosphate, and the fluorine source is sodium fluoride;
[0086] (2) drying the mixed solution in a nitrogen-protected spray freeze dryer at -30°C for 40 min to obtain a sodium ferric sulfate-coated sodium ferric sulfate fluorophosphate composite material;
[0087] (3) The composite material and acetylene black were mixed and dispersed in solvent water in a mass ratio of 98.5:1.5, and high-speed dispersion was performed under nitrogen protection at a speed of 3000 r / min and a dispersion time of 2 h, filtered, and dried to obtain a carbon / fluorophosphate sodium iron sulfate-coated sodium iron sulfate composite material precursor;
[0088] (4) The composite material precursor was sintered at 350° C. for 6 h in a nitrogen atmosphere, and the sintered material was post-treated to obtain a carbon / sodium ferric sulfate fluorophosphate coated sodium ferric sulfate positive electrode material. The thickness of the sodium ferric sulfate fluorophosphate layer of the positive electrode material was 40 nm, and the thickness of the carbon layer was 6 nm. Figure 1 This is the XRD pattern of the positive electrode material.
[0089] Example 2
[0090] The preparation method is the same as that of Example 1, except that in step (1), the molar ratio of the sodium source, iron source, phosphorus source, and fluorine source satisfies Na 3.2 Fe 1.5 (SO4) 2.9 (PO4) 0.1 F 0.1 , x=2.9.
[0091] Example 3
[0092] The preparation method is the same as that of Example 1, except that in step (1), the molar ratio of the sodium source, iron source, phosphorus source, and fluorine source satisfies Na 4.0 Fe 1.5 (SO4) 2.5(PO4) 0.5 F 0.5 , x=2.5.
[0093] Example 4
[0094] The preparation method is the same as that of Example 1, except that in step (3), the carbon source acetylene black is replaced by biomass-based carbon nanomaterials.
[0095] Comparative Example 1
[0096] A method for preparing a positive electrode material comprises the following steps:
[0097] (1) Sodium iron sulfate precursor (6 μm) was dispersed in solvent water in a mixing device, and high-speed ball milling was performed at 300 r / min under nitrogen protection for 3 h to obtain a mixed solution;
[0098] (2) drying the mixed solution in a nitrogen-protected spray freeze dryer at -30°C for 40 min to obtain a ball-milled sodium iron sulfate precursor;
[0099] (3) The ball-milled sodium ferric sulfate precursor (6 μm) and acetylene black having the same mass ratio as that of the sodium ferric sulfate precursor and acetylene black in Example 1 were mixed and dispersed in solvent water, and high-speed dispersion was performed at a speed of 3000 r / min and a dispersion time of 2 h under nitrogen protection, and the carbon-coated sodium ferric sulfate composite material precursor was obtained by filtering and drying;
[0100] (4) The carbon-coated sodium ferric sulfate composite material precursor was sintered at 350° C. for 6 h in a nitrogen atmosphere, and the sintered material was post-processed to obtain a carbon-coated sodium ferric sulfate positive electrode material.
[0101] Comparative Example 2
[0102] The preparation method is the same as that of Example 1, except that in step (1), no fluorine source is added, and the molar ratio of the sodium source, iron source, and phosphorus source satisfies Na 3.3 Fe 1.5 (SO4) 2.7 (PO4) 0.3 .
[0103] Comparative Example 3
[0104] A method for preparing a positive electrode material comprises the following steps:
[0105] (1) 97 parts of sodium ferric sulfate precursor (6 μm) and 3 parts of sodium source, iron source, phosphorus source and fluorine source were mixed and uniformly dispersed in solvent water in a mixing device, and high-speed ball milling was performed at 300 r / min under nitrogen protection for 3 h to obtain a mixed solution, wherein the molar ratio of sodium source, iron source, phosphorus source and fluorine source met Na3.6 Fe 1.5 (SO4) 2.7 (PO4) 0.3 F 0.3 , x=2.7; wherein the sodium source is sodium sulfate, the iron source is ferrous sulfate heptahydrate, the phosphorus source is sodium dihydrogen phosphate, and the fluorine source is sodium fluoride;
[0106] (2) drying the mixed solution in a nitrogen-protected spray freeze dryer at -30°C for 40 min to obtain a sodium ferric sulfate-coated sodium ferric sulfate fluorophosphate composite material;
[0107] (3) The composite material was sintered at 350° C. for 6 h in a nitrogen atmosphere, and the sintered material was post-treated to obtain a sodium ferric sulfate positive electrode material coated with sodium ferric sulfate fluorophosphate.
[0108] Preparation of button cells: The positive electrode material, separator, electrolyte, and counter electrode (sodium sheet) of the embodiment or comparative example were assembled in a glove box in sequence to obtain a CR2032 button cell.
[0109] Preparation of soft-pack batteries: The positive electrode material positive electrode sheet of the embodiment or comparative example, the hard carbon negative electrode sheet and the polyethylene diaphragm (PE+OBS diaphragm) are stacked and assembled and baked until the moisture content is qualified, the electrolyte is injected, and the battery is hot-pressed, placed at high temperature and then packaged. After volume separation, the battery is placed at room temperature to obtain a soft-pack 505060 finished battery.
[0110] Air stability evaluation: The positive electrode materials of the examples or comparative examples were placed in air for 0 weeks and 1 week, and then assembled into button batteries. The 0.1C discharge capacity was tested, and the charge and discharge voltage window was 2.0V to 4.3V. The test results are shown in Table 1.
[0111] Material rate stability: Tested on an electrochemical workstation battery test system at 25°C, with current densities of 0.1C, 0.5C, 1C, 5C, 10C, 20C, 30C, and 0.1C, and a charge and discharge voltage window of 2.0V to 4.3V. The test results are shown in Table 1 and Figure 2 .
[0112] Material cycling stability: The test was conducted on an electrochemical workstation battery test system at 25°C. The charge and discharge current density was 1C / 1C, and the charge and discharge voltage window was 2.0V to 4.3V. The test results are shown in Table 1.
[0113] Table 1
[0114]
[0115]
[0116] It can be seen from Example 1 and Comparative Example 1 that constructing a sodium ferric sulfate fluorophosphate layer can, on the one hand, improve the air stability of sodium ferric sulfate, so that the gram capacity of the positive electrode material does not decay after being placed in the air for one week; on the other hand, it can construct a better ion / electron transfer channel, so that the material still has a high gram capacity at a high rate of 30C. It can also improve the structural stability of the material under high voltage through fluoride ions and phosphate ions, and optimize the material cycle performance.
[0117] It can be seen from Example 1 and Comparative Example 2 that the introduction of only phosphate groups causes the overall discharge platform of the material to decrease. In the voltage range of 2.0 to 4.3 V, overcharging causes the material structure stability to decrease, the gram capacity is low at a high rate of 20C, and the 1C / 1C cycle stability is poor.
[0118] It can be seen from Example 1, Comparative Examples 1 and 3 that sodium ferric sulfate cannot effectively improve the air stability of the material by carbon coating alone, but the conductive network constructed by the carbon layer can improve the rate performance and cycle performance of the material to a certain extent.
[0119] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.
[0120] Although the above embodiments have been shown and described, it is understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those skilled in the art are all within the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that The positive electrode material includes a sodium ferric sulfate material, a sodium ferric sulfate fluorophosphate layer coated on the outside of the sodium ferric sulfate material, and a carbon layer coated on the outside of the sodium ferric sulfate fluorophosphate layer; the chemical formula of the sodium ferric sulfate fluorophosphate layer is Na 9-2x Fe 1.5 (SO4) x (PO4) 3-x F 3-x , where x=2.0~2.
9.
2. The positive electrode material according to claim 1, characterized in that The median particle size Dv50 of the positive electrode material is 3-8 μm; and / or, the thickness of the sodium ferric sulfate fluorophosphate layer is 10 to 100 nm; And / or, the thickness of the carbon layer is 1-10 nm.
3. A method for preparing the positive electrode material according to claim 1 or 2, characterized in that: The steps include: (1) mixing a sodium ferric sulfate precursor with a sodium source, an iron source, a phosphorus source, and a fluorine source, and then ball milling the mixture to obtain a mixed solution; (2) drying the mixed solution to obtain a sodium ferric sulfate composite material coated with sodium ferric sulfate fluorophosphate; (3) mixing the composite material in step (2) and the carbon source, dispersing the mixture, filtering, and drying the mixture to obtain a carbon / fluorophosphate-sodium ferric sulfate-coated sodium ferric sulfate composite material precursor; (4) Sintering the composite material precursor in step (3) to obtain a positive electrode material.
4. The method for preparing the positive electrode material according to claim 3, wherein: In the step (1), the mass ratio of the sodium ferric sulfate precursor to the total mass of the sodium source, the iron source, the phosphorus source and the fluorine source is 90-99:1-10; And / or, the molar ratio of the sodium source, iron source, phosphorus source and fluorine source satisfies the chemical formula Na 9-2x Fe 1.5 (SO4) x (PO4) 3- x F 3-x , x=2.0~2.9; and / or, the sodium source comprises at least one of sodium sulfate, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate or an organic acid salt of sodium; and / or, the iron source comprises at least one of a divalent iron compound; And / or, the phosphorus source includes at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium dihydrogen phosphate, sodium hexametaphosphate, and sodium pyrophosphate; And / or, the fluorine source includes at least one of sodium fluoride or ammonium fluoride.
5. The method for preparing the positive electrode material according to claim 3, wherein: In the step (1), the rotation speed of the ball mill is 200 to 500 r / min; And / or, the ball milling time is 2 to 4 hours.
6. The method for preparing the positive electrode material according to claim 3, wherein: In the step (2), the drying is carried out by spray freeze drying.
7. The method for preparing the positive electrode material according to claim 3, wherein: In step (3), the carbon source includes at least one of acetylene black, biomass-based carbon nanomaterials, glucose, sucrose, caramel, starch, carbon nanotubes, carbon quantum dots, and dextrin; and / or, the mass ratio of the composite material to the carbon source is 98-99:0.01-6; and / or, the dispersing speed is 500 to 5000 r / min; And / or, the dispersion time is 1 to 3 hours.
8. The method for preparing the positive electrode material according to claim 3, wherein: In the step (4), the sintering temperature is 300-500°C; And / or, the sintering time is 4 to 8 hours.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode material described in claim 1 or 2 or the positive electrode material prepared by the preparation method according to any one of claims 3 to 8.
Citation Information
Patent Citations
Fluorine-doped lithium ferric manganese phosphate cathode material and preparation method thereof
CN105470468A
Sodium ferric sulfate positive electrode material, preparation method thereof, positive electrode plate and sodium ion battery
CN118198303A